Estudo in vitro e in silico da atividade antifúngica dos isômeros r-(+) e s-(-)citronelal sobre fungos do gênero cryptococcus. - Costa, Aratã Oliveira Cortez (2017)
COSTA, A.O.C. In vitro and in silico evaluation of the antifungal activity of the R- (+) and S-(-) citronelal isomers, aginst fungi of the genus Cryptococcus. 2017. 52f. Dissertação (Pós-graduação em Produtos Naturais e Sintéticos Bioativos, Farmacologia). UFPB/CCS – João Pessoa – PB. Cryptococcus neoformans is an opportunistic pathogenic yeast with a wide geographical distribution, capable to infect the most varied types of animals. In humans, cryptococcosis mainly affects the central nervous system and lungs, less frequently the skin, presenting in general a serious and fatal evolution. Individuals with deficient immune systems are more likely to develop cryptococcosis, especially those afflicted with the human immunodeficiency virus. The conventional treatment of cryptococcosis uses potentially toxic antifungals for long periods and they have been target of resistance of these microorganisms, besides the high costs with the treatment. Given this panorama, the search for natural products with antifungal properties has been a promising alternative, with great attention of the students regarding the analysis of the essential oils and their constituents. Thus, the present research aimed to evaluate the biological effect of the R and S isomers of the citronellal phytoconstituent on fungi of the genus Cryptococcus, which could lead to the discovery of a molecule to the development of a new antifungal, besides contributing to obtain more information on the pharmacological potential of this phytoconstituent. MIC and MFC were determined, of the compounds, being 64 and 64 the values for R - (+) citronellal respectively, and 256 and 512, respectively, for citronellal S - (-), on fungi of the genus Cryptococcus; The antifungigram of the strains of Cryptococcus sp. was carried out with the antifungal agents amphotericin B, fluconazole and fluorocytosine where a resistance of fluconazole and flucytosine was observed; This study investigated the possible interference of monoterpenes in the study associated with the activity of these antifungal agents, noting that citronellal R did not present an apparent synergic effect, whereas S showed a much more synergistic effect, even capable of inhibiting the resistance caused by fluconazole; The microbial death curve of the R - (+) and S - (-) isomers of the citronellal phytoconstituent was determined on a previously chosen strain (FGF-3) and the fungicidal effects of the citronellal S isomer and concentration dependent fungicidal effect Of R citronelal; Its in silico variables were of good prospecting. In conclusion, the substances exhibited a good biological activity and correlation with other antifungal agents, showing synergistic effects in the association study and their in silico variables were well prospective, thus characterizing these fully viable substances to be continued their studies.